Evaluation of Roselle Hibiscus sabdariffa Flower as a Nutritive Additives on the Productive Performance of Broiler - Nasrawi, Mamdooh A.M. (The Iraqi Journal of Veterinary Medicine, 2013)
The study included 300 unsexed broiler chicks (Hubbard) were used to evaluate (Roselle Flower) as a feed additives on the productive performance of broiler. The chicks were divided into five groups with three replicates (20 birds in each) and fed on five diets. Diet 1 (control group) dried Roselle flower powder were supplemented to the diet 2, 3, 4 and 5 as 0.25, 0.5, 0.75 and 1% respectively. The result revealed that a significant (P<0.05) increase in body weight, body weight gain, feed consumption and improvement in feed conversion ratio. Although the differences between groups for edible parts percent were not significant (Heart, Liver and Gizzard). The hematological values PCV%, RBC, WBC and H/L ratio were increased significantly (P<0.05) and cholesterol values decreased significantly as compared with control group. It can conclude that Roselle as other herbal plants may be considered as a feed additive in broiler diet would improve the productive performance, hematological and biochemical values of broiler. Diet Roselle flower supplementation of (1g/kg) might be acceptable for achieving optimum broilers performance.